TEST APPLICATION OF OIL PALM EMPTY FRUIT BUNCH COMPOST AND DRIED DECANTER SOLID ON THE GROWTH AND RESULTS OF SPRING ONION PLANT (ALLIUM FISTULOSUM L.) HOLE VARIETY: UJI APLIKASI KOMPOS TANDAN KOSONG KELAPA SAWIT DAN DRIED DECANTER SOLID TERHADAP PERTUMBUHAN SERTA HASIL TANAMAN BAWANG DAUN (Allium Fistulosum L.) VARIETAS LUBANG - Soni Setiawan; Mahdalena; Hamidah (Universitas Widya Gama Mahakam, 2021)
Increased production of oil palm empty fruit bunches results in large quantities of waste that have not been used optimally. One of the wastes produced from oil palm mills is oil palm empty fruit bunches and dried decanters solid. Waste from oil palm empty fruit bunches can be made into compost. This type of waste can be used as organic fertilizer for oil palm plants. The function of organic fertilizer is to improve soil structure, soil texture, aeration and increase the soil's absorption capacity. Organic fertilizers also function as stimulants to improve the health of plant roots and provide food for microorganisms that can maintain the soil in a healthy and balanced condition. The purpose of this study was to determine the effect and interaction of applications of oil palm empty fruit bunch compost and dried decanters solid on the growth and results of spring onion plant (Allium fistulosum L.) hole variety. The study was conducted in the Experimental Garden of the Faculty of Agriculture, Widya Gama Mahakam Samarinda University. The study was conducted for ± 6 months starting in January to July 2018. This study used a randomized block design (RBD) with a 4 x 4 Factorial Experiment consisting of 3 replications. The first factor is the application of oil palm empty fruit bunch compost (K) namely K0 (control), K1 (70 g/polybag), K2 (120 g/polybag), and K3 (170 g/polybag). The second factor is the application of dried decanter solid (S) namely S0 (control), S1 (65 g/polybag), S2 (115 g/polybag), and S3 (165 g/polybag). The results showed that the application of oil palm empty fruit bunch compost and dried decanter solid as well as the interaction combination of treatment had a very significant effect on the observed variable height of plants per clump (cm), fresh weight of plants per clump (g), and had no significant effect on the observation variables leaves per clump (sheet) as well as the number of tillers per clump (fruit).